2021
DOI: 10.1159/000510943
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide Supplementation Attenuates Renal Interstitial Fibrosis via Boosting the Activity of Sirtuins

Abstract: <b><i>Background:</i></b> Progressive tubulointerstitial fibrosis (TIF) is the final common pathway leading to ESRD. There is an urgent need to develop effective approaches slowing the progression of TIF. Previous studies showed that systemic supplementation of nicotinamide (NAM) increases renal NAD<sup>+</sup> and reverses ischemic-reperfusion induced acute renal injury. However, the role and mechanism of NAM in TIF has been unclear. <b><i>Methods:</i><… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…We have previously reported that NMN administration improves albuminuria in diabetic nephropathy 32 . Additionally, NAM administration improves renal fibrosis 33 , 34 . Taken together, decreased NAD + and precursors for NAD + synthesis in CKD could contribute to CKD progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported that NMN administration improves albuminuria in diabetic nephropathy 32 . Additionally, NAM administration improves renal fibrosis 33 , 34 . Taken together, decreased NAD + and precursors for NAD + synthesis in CKD could contribute to CKD progression.…”
Section: Discussionmentioning
confidence: 99%
“…Administrating NAD + precursors and methionine to augment this effect might provide a more robust explanation of the underlying mechanism. As for NAD + precursors, it has been reported that NAM administration improves renal fibrosis 33 , 34 . On the other hand, methionine has been reported to increase renal tubular damage 53 , and methionine administration does not always increase SAM/SAH 54 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, NAM treatment was shown to (1) inhibit cytokine responses (IL-1β, IL-6, IL-8, TNFα) to endotoxin in whole human blood ( Ungerstedt et al., 2003 ), (2) to diminish the IFN-γ-induced expression of adhesion proteins such as intercellular adhesion molecule-1 (ICAM-1) on thyroid and endothelial cells, which presumably reduces lymphocyte homing to inflammatory sites ( Hiromatsu et al., 1992 , 1993 ), and (iii) to inhibit cytokine-induced MHC class II antigens on pancreatic cells ( Yamada et al., 1990 ). Administration of NAM in vivo attenuated cytokine induction in ischemia/reperfusion-induced lung injury in rats ( Su et al., 2007 ); alleviated the progression of kidney disease in mouse models by reducing inflammation and fibrosis ( Kumakura et al., 2021 ; Zhen et al., 2021 ); and reduced high-fat diet-induced steatosis and inflammation in mice ( Mitchell et al., 2018 ). However, these studies did not investigate whether NAM has a direct effect as an anti-inflammatory molecule.…”
Section: Discussionmentioning
confidence: 99%
“…NAM (250 mg/kg i.p. 3 days before UUO and continuing to Day 7) also reduced fibrosis and Neutrophil gelatinase-associated lipocalin (NGAL) levels in mice at Day 7 [ 32 ]. Moreover, in murine aristolochic acid nephropathy NAM (500 mg/kg, i.p.…”
Section: Vitamin B3 As a Kidney Protective Strategy In Experimental Ckdmentioning
confidence: 99%
“…Moreover, in murine aristolochic acid nephropathy NAM (500 mg/kg, i.p. 1 day before and continuously up to Day 14) reduced tubular injury and cytokine expression on Day 15, but this effect was weaker than in the UUO model [ 32 ]. Drinking NAM (0.3, 0.6 or 1.2% NAM) from Day 0 until the end of study (6 weeks) improved kidney function and decreased tubular injury and inflammation in murine adenine-induced CKD.…”
Section: Vitamin B3 As a Kidney Protective Strategy In Experimental Ckdmentioning
confidence: 99%